Prenatal exposure to endocrine-disrupting chemicals and childhood atopic dermatitis: epidemiological evidence - Chen, Yuxin; Zhang, Le; Yang, Ting; Chen, Limei (Frontiers in Microbiology, 2025)
Atopic Dermatitis (AD) is a highly prevalent chronic inflammatory disease in children, and its global prevalence is continually rising. However, data from the past decade indicate that this overall trend masks a disparity: while the prevalence has plateaued in high-income countries, it has shown a significant upward trend in low- and middle-income countries. Prenatal exposure to endocrine-disrupting chemicals (EDCs) is an environmental factor of growing scientific concern. Key EDCs of interest include per- and polyfluoroalkyl substances (PFAS), phenolics such as bisphenol A (BPA), parabens, and triclosan (TCS), as well as phthalate esters (PAEs). Although epidemiological studies indicated an association between prenatal EDCs exposure and an increased risk of offspring developing AD, key challenges remain unresolved, including population heterogeneity, methodological variations in exposure assessment, and elucidation of the underlying mechanisms. The review summarized the epidemiological evidence linking prenatal EDCs exposure to childhood AD, aiming to provide a theoretical basis for the early prevention of AD. Furthermore, it highlighted the future need to integrate multi-omics technologies with prospective cohort studies to elucidate the effects of mixed EDCs exposures and identify critical intervention windows.